MARKETING GAMES AND SENSITIVITY ANALYSIS FOR ANY NUMBER OF COMPANIES - Amir, Almira; Simanjuntak, Ruth Mayasari; Suzana, Yenny; Lubis, Riri Syafitri; Syarah, Fatmah; Fajriana, Fajriana; Zahedi, Zahedi (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2026)
In the business world, advertising plays a crucial role in shaping market dynamics. This study analyzes advertising competition among companies by calculating the optimal profits for two to four competitors and postulating a general formula for a larger number of companies. Sensitivity analysis is employed to observe how changes in advertising parameters affect profits. The simulation results indicate that in the case of four companies, the optimal spending (Xopt) ranges from 137246 to 191288, while the optimal profit (Popt) ranges from 38693.1 to 92702. The sensitivity analysis shows that companies with higher advertising effectiveness achieve greater profits, whereas those with lower effectiveness tend to experience reductions in both allocation and profit. With the aid of Maple and Excel, this research extends previous advertising competition models by providing a comprehensive framework for optimizing advertising budgets in oligopolistic markets.